PELATIHAN PENULISAN E-MODUL PADA GURU-GURU SMP NEGERI 1 KOTA JAYAPURA PAPUA - Jonner Nainggolan; Virman (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
ervice activities for writing modules and e-modules for teachers during the COVID-19 pandemic are needed because learning is carried out online. The purpose of this community service activity is to increase the knowledge of teachers in writing modules and e-modules. Community service activities were carried out for the teachers of SMP Negeri 1 Jayapura City. Method of implementation: with the method of lectures, discussions, questions and answers, and exercises. The results of community service activities: (1) There are differences in knowledge about modules and e-modules for teachers of SMP Negeri 1 Jayapura City before and after the training activities. (2) There was an increase in knowledge about modules and e-modules among teachers at SMPN 1 Jayapura City with an average n-gain of 0.55 including the medium category.